(untitled) (Asian Education Studies, 2016)
Offering English-medium-instruction (EMI) courses in universities and colleges has gradually become a national policy in Taiwan. However, many students struggle in EMI courses. One possible reason is that Taiwanese students do not have sufficient English competence to understand academic text and academic lectures in English. Reciprocal teaching (RT) has been considered an effective way to increase students’ reading comprehension in many elementary and junior-high school language classrooms. Yet, few studies have been done for tertiary-level students. Thus, this small-scale pilot study was conducted to examine whether there was an effect of reciprocal teaching on students’ academic performance. A class of 62 students enrolling in Educational Psychology was taught first in a traditional lecturing style (about 2 months) and later in RT (about 2 months). Data was collected at four time periods (2 in-class quizzes and 2 achievement tests). Results of one-way repeated ANOVA showed that there was a significant difference on students’ test score before and after the intervention. This suggests that the RT technique may help Taiwanese students comprehend academic text and further help them learn in EMI courses.